Relationship and Innovation Marketing: A Study of Graphic Segment Organizations in Natal-Rn (Revista Brasileira Multidisciplinar, 2013)
This work aims to analyze, through a quantitative research with the application of questionnaires with closed questions, the use of the Relationship dimension, one of the 13 dimensions that make up the Innovation Radar instrument, a method applied to measure the degree of innovation of enterprises. The analyzed companies, as a whole, seven graphics assisted by the Innovation Local Agents Program at Rio Grande do Norte, don't have effective actions to keep the customers, they know their needs and expectations about the product / service, but, despite that, they haven't innovated their practices to improve and establish lasting relationships. It was possible to notice that entrepreneurs are slowly absorbing the culture of providing facilities and resources that meet the desires and needs of their customers. We conclude that companies are open to new knowledge, concepts and changes, which is a cultural incentive for innovation and new approaches that will propitiate the growth and the expansion of the sector, using practices to improve the relationship with their customers.
Keywords: Innovation Radar; Relationship Dimension; Relationship; Graphic Companies; Rio Grande do Norte.